2011
DOI: 10.1099/ijs.0.020909-0
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium humireducens sp. nov., an alkaliphilic, humic acid-reducing bacterium isolated from a microbial fuel cell

Abstract: A novel halotolerant, alkaliphilic, humic acid-reducing bacterium, designated MFC-5 T , was isolated from a microbial fuel cell that was fed continuously with artificial wastewater (pH 10.0). Cells were Gram-positive-staining, facultatively anaerobic, non-fermentative, non-motile rods and had a G+C content of 59.0 mol%. Microbial growth was observed with ,13 % (w/v) NaCl (optimum 10 %), at pH 7.0-11.0 (optimum pH 9.0) and at 25-45 6C (optimum 37 6C). Strain MFC-5 T was active in the anaerobic reduction of a hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 32 publications
(28 reference statements)
2
41
0
3
Order By: Relevance
“…Microbial growth supported by iron reduction has been observed at pH values up to 11 (Ye et al 2004;Pollock et al 2007;Wu et al 2011) suggesting that the brown soil with a pH value >12 is a rather marginal environment for iron reducing bacteria. However an average pH value does not fully characterise the geochemical environment of a soil, where there may be microenvironments.…”
Section: Discussionmentioning
confidence: 97%
“…Microbial growth supported by iron reduction has been observed at pH values up to 11 (Ye et al 2004;Pollock et al 2007;Wu et al 2011) suggesting that the brown soil with a pH value >12 is a rather marginal environment for iron reducing bacteria. However an average pH value does not fully characterise the geochemical environment of a soil, where there may be microenvironments.…”
Section: Discussionmentioning
confidence: 97%
“…nov (Wu et al 2010), and Geobacter metallireducens (Lovley et al 1996b). To the best of our knowledge, this study, for the first time reported a strain of P. aeruginosa could utilize AQDS as the sole electron acceptor for their growth under anaerobic conditions.…”
Section: Effect Of Electron Donors On Aqds Reduction By Strain Pah-1mentioning
confidence: 94%
“…For the reconstruction of phylogenetic trees almost full-length 16S rRNA gene sequences (>1400 bp) that were closely related to strain VDS11 T were retrieved from GenBank and validated using the EzTaxon-e Server (Kim et al, 2012). Strain VDS11 T showed highest sequence similarity with Corynebaterium humireducens MFC-5 T (98.7 %, 1401 bp) (Wu et al, 2011) and Corynebacterium nasicanis 2673/12 T (98.4 %, 1382 bp) (Baumgardt et al, 2015). The percentage pair wise sequence similarity of strain VDS11…”
mentioning
confidence: 99%